Tahfidzul Qur'an di Pondok Pesantren Moderen Ainul Yaqin Batagak Kecamatan Sungai Pua Kabupaten Agam - Sari, Nila; Junaidi, Junaidi (Lembaga Yasin AlSys, 2023)
This article discusses the Tahfidzul Quran at the Ainul Yaqin Batagak Modern Islamic Boarding School, Sungai Pua District, Agam Regency. In this study, researchers used a form of qualitative research. Researchers used interview techniques, documentation, and observation. The data collected was then analyzed using qualitative analysis techniques. From the research that the author did, it can be concluded that, Tahfidzul quran in the modern pesantren ainul yaqin batagak which has been established for approximately 14 years is to print a thousand tahfidzul quran according to the program launched by the Ministry of Religious Affairs. The time of tahfidzul quran in the modern pesantren ainul yaqin batagak is held starting from 06.55-07.30 WIB. The activity is carried out in each class which is directly guided by the group leader. In this case there is no special management but the memorization is left to the students both in depositing and technique. The material given to students is evenly distributed, namely starting from grades 7-12 must complete memorization of Surah al-Baqarah. The method of tahfidzul quran given to students is not determined, but rather given freedom to students to choose. The evaluation of tahfidzul quran is carried out in 3 stages, the first through the group leader once a week, the second through the coach once a month, and once a semester before the exam is held. The obstacles faced during tahfidzul quran are related to the narrow time and student discipline.